2004
DOI: 10.1097/00126334-200403010-00011
|View full text |Cite
|
Sign up to set email alerts
|

Injecting Equipment Sharing Among Injecting Drug Users in Togliatti City, Russian Federation

Abstract: Findings highlight the delicate balance in HIV prevention between potentially competing strategies of law enforcement and syringe distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Disclosure and secondary prevention are rare among IDUs in some Eastern European countries (Booth et al 2004;Gore-Felton et al 2003;Amirkhanian et al 2003;Rhodes et al 2004b). In this study, we found strong disclosure and secondary prevention norms for HIV, HBV and HCV.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Disclosure and secondary prevention are rare among IDUs in some Eastern European countries (Booth et al 2004;Gore-Felton et al 2003;Amirkhanian et al 2003;Rhodes et al 2004b). In this study, we found strong disclosure and secondary prevention norms for HIV, HBV and HCV.…”
Section: Discussionsupporting
confidence: 48%
“…Hungarian IDUs' perception of risk and their injecting and sex risk behaviors are based on trust and on personal risk assessment: equipment sharing "never" occurs -except with few close and trusted friends (Rhodes et al 2004a), and condoms are rarely used in their monogamous sexual relationships. In Russia and the Ukraine, even though many IDUs perceive their infection risk as low, they often have high-risk injecting and sex behaviors and networks: they commonly share syringes, even with people whom they do not know well (Abdala et al 2003;Booth et al 2004;Amirkhanian et al 2003;Rhodes et al 2004b), and they have large numbers of sex partners and concurrent partners (Hamers and Downs, 2003). However, sharing spoons and filters was common and viewed as less risky among participants of this study (Huo et al 2005;Millson et al 2003).…”
Section: Discussionmentioning
confidence: 70%
“…This seems to differ from sex partner turnover among young IDUs found by some studies in the US and in Russia, where some young IDUs have more frequent turnover and/or concurrent partnerships in their sexual networks than do the young IDUs in Budapest that are reported on here. [20][21][22][23][24][25][26] We found the difference in how and why SI-IDUs and M-IDUs stop using drugs noteworthy, especially the role of being in drug treatment and incarceration among M-IDUs. 27 M-IDUs reported stopping injecting when in prison, which is consistent with our previous work among Hungarian inmates indicating little drug use and/or drug injecting in Hungarian prisons.…”
Section: Discussionmentioning
confidence: 79%
“…In summary, current research indicates that IDUs and risky drinkers in Russia are experiencing notable rates of HIV/STI and report notable HIV risks, including multiple partners, sex trade involvement and unprotected sex (Benotsch et al 2004;Krupitsky et al 2004;Platt et al 2005;Rhodes et al 2004;Somlai et al 2002;Takacs et al 2006;Karapetyan et al 2002). Such research has not, however, examined associations between HIV/STI risk histories and condom use.…”
Section: Sexual Transmission Of Hiv Infection Within Russia Is Assumementioning
confidence: 92%
“…Studies with IDUs recruited from urban centers within Russia have found that the majority reports recent sexual activity, multiple partners and non-condom use, particularly with steady sex partners (Rhodes et al 2004;Somlai et al 2002;Takacs et al 2006). The epidemic has been propelled even further via the link between injection drug use and sex work, particularly for female IDUs.…”
Section: Sexual Transmission Of Hiv Infection Within Russia Is Assumementioning
confidence: 99%